2010
DOI: 10.1164/rccm.200909-1338oc
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, Use of Moist Snuff, and Risk of Chronic Inflammatory Diseases

Abstract: Smokeless tobacco does not increase the risk of chronic inflammatory diseases, suggesting that inhaled nonnicotinic components of cigarette smoke are more important than nicotine itself in the etiology of these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
122
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(135 citation statements)
references
References 51 publications
9
122
0
4
Order By: Relevance
“…It does, however, carry the risk of exposure to nicotine, heavy metals, and contaminating microorganisms and their products, with the levels of blood and urine nicotine/cotinine being comparable to those of smokers [81][82][83][84][85]. Although studies to date are somewhat limited, those that have been reported did not, however, detect an association between usage of snuff and risk of development of either ACPApositive or ACPA-negative RA, or for increased disease severity [86][87][88]. All of these studies were performed in Sweden and involved users of orally-applied moist snuff.…”
Section: Smokeless Tobacco (Snuff)mentioning
confidence: 97%
“…It does, however, carry the risk of exposure to nicotine, heavy metals, and contaminating microorganisms and their products, with the levels of blood and urine nicotine/cotinine being comparable to those of smokers [81][82][83][84][85]. Although studies to date are somewhat limited, those that have been reported did not, however, detect an association between usage of snuff and risk of development of either ACPApositive or ACPA-negative RA, or for increased disease severity [86][87][88]. All of these studies were performed in Sweden and involved users of orally-applied moist snuff.…”
Section: Smokeless Tobacco (Snuff)mentioning
confidence: 97%
“…The biological mechanisms that would link smoking to the pathogenesis MS are elusive. Nicotine, however, might not be the sole culprit since studies have shown that use of tobacco snuff does not increase the risk of MS [83,84].…”
Section: Smokingmentioning
confidence: 99%
“…It is thus possible to assume that smoking plays a role in the development of NC, even when smoking appears to cause multiple sclerosis in other ways than through the mediation of nicotine (Carlens et al, 2010).…”
Section: )mentioning
confidence: 99%
“…Some studies report that NC is associated with higher levels of impulsiveness and the so-called sensation-seeking behaviour in this condition (Dimitrova et al, 2011), which might explain increased tendency to smoke. Smoking is a risk factor for development and progression of multiple sclerosis (Carlens et al, 2010;Wingerchuk, 2012;Hedstrom et al, 2013) and other inflammatory diseases such as rheumatoid arthritis, Crohn's disease, ulcerative colitis, and…”
Section: Introductionmentioning
confidence: 99%